IN VITRO ANTIBACTERIAL ACTIVITY OF GREEN TEA EXTRACT AGAINST MULTIDRUG-RESISTANT BACTERIA - MEHTA, ABHISHEK; SAXENA, GAURAV; JAIN, ARTI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: This study aimed to evaluate the antimicrobial activity of ethanolic extract of green tea (Camellia sinensis) against multidrug-resistant strains of the pathogenic bacteria: Extended-spectrum-β-lactamase (ESBL) producing Enterobacteriaceae, Carbapenem-resistant Enterobacteriaceae (CRE), and Metallo-β-lactamase (MBL) producing Pseudomonas aeruginosa strains. Methods: In this cross-sectional study, the antibacterial activity of ethanolic extract of commercial green tea against the 23 multidrug-resistant test strains was evaluated by the Agar well diffusion method, and the minimum inhibitory concentration of the extract for the test strains was determined by Agar plate dilution method. Results: Ethanolic extract of green tea was found to exhibit a remarkably significant antimicrobial activity against the ATCC (American type culture collection) control strains: E. coli ATCC 25922 and P. aeruginosa ATCC 27853 with slightly higher activity against later as compared to the former. The extract exhibited a significant antibacterial activity against multidrug-resistant bacterial strains. The highest activity was shown against ESBL producing strains, followed by CRE strains and the least activity against MBL producers. Conclusion: This study strongly depicts that the ethanolic extract of green tea exhibits significant antibacterial activity even against multidrug-resistant strains. Hence, such plant extracts could be a potential source of bioactive lead compounds that could be utilized in developing herbal antimicrobials as an alternative strategy for tackling the problem of antimicrobial resistance.